A Generic Review on Effective Intrusion Detection in Ad hoc Networks - G. Gopichand; RA.K. Saravanaguru (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Ad hoc network is specifically designed for the establishment of a network anywhere and anytime, which does not have any fixed infrastructure in order to support the mobility of the users in the network. The network is established without using any access points or base stations for communication implemented in multi hop schemes. Hence we call an Ad hoc network as a collection of nodes which are mobile in nature with a dynamic network infrastructure and forms a temporary network. Because of dynamic topological changes, these networks are vulnerable at the physical link, and they can easily be manipulated. An intruder can easily attack the Ad hoc network by loading the network resources which are available, such as wireless links and energy (battery) levels of other users, and then starts disturbing all the users. This paper provides a comparative survey on the various existing intrusion detection systems for Ad hoc networks based on the various approaches applied in the intrusion detection systems for providing security to the Ad hoc network.